Intravascular papillary endothelial hyperplasia of larynx: case report and literature review of all head and neck cases - Tedla, Miroslav; Bežová, Miroslava; Biró, Csaba; Tedlová, Eva; Eng, Chee-Yean; Zeleník, Karol (Otolaryngologia polska, 2014)
Intravascular papillary endothelial hyperplasia (IPEH) is a benign lesion of a vascular origin that is caused by excessive proliferation of endothelial cells in blood vessels or vascular malformations. It is a rare entity that can present in any region of the body, but with particular predilection to the head and neck region and the extremities. We also present the results of the English literature search, which to our knowledge are all the published cases of IPEH in the head and neck region (No=213). IPEH has not been reported to arise from the glottic region previously. We present a first case of IPEH arising from the vocal fold of a 48-year-old male. Histological differential diagnosis of IPEH includes several entities, most importantly angiosarcoma. Presentation and histology are discussed. The main treatment option is a complete surgical resection. Prognosis of IPEH is excellent, with the exception of some intracranial cases.
Keywords: hyperplazie; Humans; diferenciální diagnóza; lidé středního věku; Intravascular papillary endothelial hyperplasia; Head; krk; Glottis; Diagnosis, Differential; lidé; larynx; Hyperplasia; hlava; Male; Middle Aged; prognóza; Neck; Larynx; mužské pohlaví; Head and neck; Prognosis